Methods to Detect Inadequate Bit Cleaning in Diamond Drilling. - Su, Kwong Lee (Curtin University, 2024)
Drilling is essential for resource extraction but is often costly, time-intensive, and prone to challenges like inadequate bit cleaning, which reduces efficiency, increases bit wear, and raises operational costs. Beyond a critical penetration rate, debris removal becomes inefficient, leading to performance drops. Current solutions rely on driller experience without standardized guidelines. This research develops a real-time algorithm to analyze drilling data, detect inefficient conditions, and recommend parameter adjustments to enhance efficiency and reduce costs.